Fouling Mechanism of Ultrafiltration Polypiperazine Amide Membrane during Catalytic Conversion of Thiophene in Petroleum Fraction via Hybrid Membrane Photocatalytic Reactor (MPR) - Abdullah, Faatihah; Hairom, Nur Hanis Hayati (Progress in Engineering Application and Technology, 2021)
In many centuries, petroleum industry has been established and greatly developed to produce many types of products such as gasoline, diesel, naphtha, kerosene and fuel oil. These products are obtained from the refinery and distillation of the crude oil. However, sulfur pollutants like thiophene subsequently contained in the petroleum products. Thiophene can cause deactivation of catalysts, promote formation of coke and damage the equipment including corrode the pipelines and pumping systems used in refining process. Membrane photocatalytic reactor (MPR) is the promising method that can degrade the sulfur pollutant in petroleum fraction. The zinc oxide-Cymbopogon citratus (ZnO-CC) nanoparticles was used due to its good photodegradation properties as well as the use of ultrafiltration polypiperazine amide (UF-PPA) membrane in this hybrid system. The drawback in utilization of the membrane is membrane fouling mechanisms that included complete blocking, intermediate blocking, standard blocking and cake formation may occurred during the photodegradation of thiophene and eventually affect the membrane flux decline. Therefore, this study aims to elucidate the correlation between flux decline and mechanism fouling of membrane via model fitting in MATLAB software. It was found that both stage1 and 2 shown that the occurrence of cake formation under pH 10, initial concentration of 50 ppm and ZnO-CC loading of 0.08 g/L. However, the cake formation may occur rapidly in first stage as the K value (1.2×10-3) is higher than K value (7.8×10-4) in second stage. As the result, the flux declines constantly leading to the highest value of flux decline (0.35).  Whereas the lowest flux decline (0.09) was under solution pH 2, initial concentration of 100 ppm and photocatalyst loading of 0.08. The initial concentration and photocatalyst loading also the parameters that can affect the thiophene degradation, but it is not critical as pH.